Perspectives on the Horak debate (湖洛論爭): reviews and suggestions - Na, Jonghyun (International Journal of Korean Humanities and Social Sciences, 2023)
This paper analyzes the perceptions shared in previous studies by dividing them into two categories and examines how to grasp the Horak debate and the academia of the late Joseon Dynasty. First, the appropriateness of describing the late Joseon academia in terms of the doctrinized Neo-Confucianism and anti-Neo-Confucianism is examined. The consciousness and research methods of the Horon, which are considered to be typical of the doctrinized Neo-Confucianism, was analyzed. Next, whether the political positions of Horon and Rakron before and after the Horak debate can be categorized as conservative or open-minded is examined. The actual political positions of the main debaters of the Horak debate was carefully reviewed. With this discussion, this paper argued that the existing understanding of the Horak debate is largely based on an overly schematic framework, and that it is necessary to move beyond this framework and examine the context of the period in a more nuanced way.